Fintech adoption and zakat efficiency: The moderating role of Islamic bank performance - Nur Suci Ismiyati Mei Murni; Kautsar Riza Salman; Entis Sutisna (Faculty of Islamic Economics and Business, UIN Salatiga, 2025)
Fintech provides innovative solutions to improve the efficiency of zakat collection and distribution through digital payment systems, online applications, and blockchain technology. However, the effectiveness of fintech adoption may depend on the internal financial conditions of Islamic banks. This study examines the effect of fintech adoption on zakat efficiency and investigates the moderating role of bank financial performance in Indonesian Islamic banks. Using a quantitative approach with panel data from 12 Islamic Commercial Banks during the 2015–2024 period, fintech adoption is measured through a fintech adoption index derived from annual reports, while zakat efficiency is measured using the zakat distribution ratio. Financial performance is represented by Return on Assets (ROA) and Return on Equity (ROE). The findings reveal that fintech adoption does not directly affect zakat efficiency. However, ROA strengthens the relationship between fintech adoption and zakat efficiency, whereas ROE weakens it. These results indicate that the effectiveness of fintech in supporting Islamic banks’ social functions depends more on efficient asset management than equity performance. This study highlights the importance of integrating digital transformation with sound financial management to optimize zakat management